2017
DOI: 10.1590/0104-530x1413-16
|View full text |Cite
|
Sign up to set email alerts
|

Análise do gerenciamento de resíduos sólidos e proposição de melhorias: estudo de caso em uma marcenaria de Cariacica, ES

Abstract: Resumo: O presente trabalho investiga o gerenciamento de resíduos sólidos em uma empresa moveleira sediada no município de Cariacica, ES. Primeiro, foram obtidas informações acerca do setor moveleiro da região, por meio de material bibliográfico, junto à Associação de Indústrias e Produtos de Insumos do Setor Mobiliário de Cariacica (AMOVEL), à Secretaria Municipal de Desenvolvimento Econômico e Turismo (SEDETUR) da Prefeitura de Cariacica e ao Sindicato das Indústrias de Madeira e Atividades Correlatas em Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…Como demonstração no gráfico, os dados apresentados permitem evidenciar que 24,5% de matéria prima se transformam em resíduos de madeira ao final do processo. Pôde-se observar que essa perda é significativa ao compará-la com estudos realizados por Caetano et al (2017), em uma marcenaria de pequeno porte em Cariacica-ES, na qual se constatou uma perda superior a 20%.…”
Section: Resultsunclassified
“…Como demonstração no gráfico, os dados apresentados permitem evidenciar que 24,5% de matéria prima se transformam em resíduos de madeira ao final do processo. Pôde-se observar que essa perda é significativa ao compará-la com estudos realizados por Caetano et al (2017), em uma marcenaria de pequeno porte em Cariacica-ES, na qual se constatou uma perda superior a 20%.…”
Section: Resultsunclassified
“…Part of these raw materials is lost in manufacturing in the form of waste, which is estimated at 10% of the total mass [21]. However, a study carried out at a medium-sized furniture industries in Espírito Santo showed a percentage loss of over 20% [22].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A study by the Brazilian Association of Public Cleaning and Special Waste Companies cited in ABRELPE (2016) indicates that between 2014 and 2015 an approximate increase of 12,692 tons of MSW per day was generated in the Amazon and, of 450 municipalities, only 258 in the northern sub-region of Brazil maintained the selective collection programme, revealing a significant risk to the developmental advance in the scenario under review. Caetano et al (2017) insists that, in the treatment of solid waste, its weight and volume before and after treatment should be measured to gather important information on the efficiency of the procedures applied, the amount of waste that would eventually go to landfill and the average useful life of these units.…”
Section: Sourcementioning
confidence: 99%